High Prevalence of Colistin Resistance and mcr-1 Gene in Escherichia coli Isolated from Food Animals in China - Huang, Xianhui; Yu, Linfeng; Chen, Xiaojie; Zhi, Chanping; Yao, Xu; Liu, Yiyun; Wu, Shengjun; Guo, Zewen; Yi, Linxian; Zeng, Zhenling; Liu, Jian-Hua (Frontiers in Microbiology, 2017)
The objective of this study was to determine the minimal inhibitory concentration of colistin for Escherichia coli from food animals and the possible underlying colistin resistance mechanisms. During 2007–2014, 4,438 E. coli isolates of food animal origins were collected. The susceptibility of colistin was tested by the agar dilution method. Mutations in pmrA, pmrB, and mgrB and the presence of mcr-1 gene were determined by PCR and DNA sequencing. Complementation experiments were carried out to evaluate the contribution of the mutations to colistin resistance. There was a high frequency of colistin resistance in E. coli from pigs on farm (24.1%) and at slaughter (24.3%) in 2013-2014, followed by chickens on farm (14.0%) and at slaughter (9.5%). The resistance frequency of E. coli in cow isolates was the lowest (0.9%). MIC distribution for colistin showed that most isolates (75.2%) were distributed at 0.25 mg/L -0.5 mg/L, followed by 4 mg/L -8 mg/L (16.8%). Compared with the isolates from pigs and chickens recovered during 2013-2014, E. coli isolates collected during 2007-2008 (5.5%) and 2010-2011 (12.4%) showed significantly lower frequency of colistin resistance (P<0.05). DNA sequencing and complementation experiments failed to detect any insertion inactivation or mutation in pmrA, pmrB, and mgrB associated with colistin resistance. However, 91.0% colistin-resistant isolates were positive for mcr-1. The high frequency of colistin resistance and mcr-1 gene among E. coli isolates from food animals in China urged the need to minimize potential risks of colistin resistance development and the spread of mcr-1 gene.